Low-cost marine biomass carbon as a high-performance electrocatalyst for vanadium redox flow battery. Issue 12 (26th September 2022) - Liu, Yongguang; Jiang, Qingchun; Jiang, Yingqiao; Lv, Yanrong; He, Zhangxing; Dai, Lei; Wang, Ling
ABSTRACT: We found that cuttlefish bone is a three-dimensional organic framework material containing carbon, nitrogen, and oxygen. Therefore, we prepared marine biomass porous carbon (MBPC) nanomaterials by carbonization and pickling with cuttlefish bone as carbon source. Then, a simple air oxidation activation (AOA) method was used to react MBPC with air at 300 °C for 1, 3, and 8 h to obtain MBPC-A1, MBPC-A3, and MBPC-A8, respectively. MBPC series samples obtained are carbon nanosheets with different thicknesses, defect degrees, and N and O contents. Moreover, the samples have a large specific surface area. They were used as electrode catalysts for redox reactions of VO 2+ /VO2 + and V 3+ /V 2+ in vanadium redox flow battery (VRFB). Electrochemical tests show that the modified electrodes have good catalytic activity. MBPC-A3 modified electrode shows the best electrochemical performance. Charge-discharge test results show that the discharge capacity of modified cell is significantly increased, and the energy efficiency can be improved from 74.97% to 79.63%. Biomass cuttlefish bone as a carbon source has the advantages of being both inexpensive and widely available. Meanwhile, the AOA method has simple experimental conditions, which is expected to be widely used in the preparation of biomass nanomaterials in the future.